Spectrality Policies in Raul Ruiz Cinema: A Reading From a Philosophy of Disappearance - Vera Peñaloza, Adolfo (Revista de Humanidades de Valparaíso, 2013)
The cinematographic work of Raul Ruiz, filmmaker, writer, playwright and stage designer, chilean exiled in France since the late 70’s and deceased in 2011, at first sight not appear as a political work. Usually classified with the labels of "neosurrealistic" or "fantasy film", his work, since not refer to a specific and identifiable reality from the positivist sociology standpoint, will have not most interest to analyze and think what the political "emergency" of our times requires. However, from a philosophical analysis of what the political demise implies for the thinking of the community, of the event and the History, analysis that mark the question of spectrality as the key for the understanding what was then (not) occurs, this work - which dilutes all limit between the real and the unreal - appear as one of the most important of our time.